1990
DOI: 10.1111/j.1432-1033.1990.tb19410.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies on the metal‐ion‐binding sites of Co2+‐substituted D‐xylose isomerase from Streptomyces rubiginosus

Abstract: The coordination sphere of the two metal-binding sites/subunit of the homotetrameric D-XylOSe isomerase from Streptomyces rubiginosus has been probed by the investigation of the Co2+-substituted enzyme using electronic absorption, CD and magnetic circular dichroic spectroscopies in the visible region. The spectrum of the high-affinity site (B site) has an absorption coefficient, E~~~, of 18 M-' cm-', indicating a distorted octahedral complex geometry. The spectrum of the low-affinity site (A site) shows two ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
42
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Addition of Zn2+, Cd", or Pb" to the metal-free apoenzyme does not restore activity. However, their addition in the presence of saturating Mg2+ concentrations inhibits the enzyme almost completely [7].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Addition of Zn2+, Cd", or Pb" to the metal-free apoenzyme does not restore activity. However, their addition in the presence of saturating Mg2+ concentrations inhibits the enzyme almost completely [7].…”
mentioning
confidence: 99%
“…Addition of Zn2+, Cd", or Pb" to the metal-free apoenzyme does not restore activity. However, their addition in the presence of saturating Mg2+ concentrations inhibits the enzyme almost completely [7].Spectroscopic studies on the Co2+-substituted Xyl isomerase revealed that each subunit contains two different binding sites [7, 121. The high-affinity site of Co2+, denoted as the B site, has a distorted octahedral coordination geometry, whereas the low-affinity site, denoted as the A site, seems to be pentacoordinated.…”
mentioning
confidence: 99%
See 3 more Smart Citations